KINERJA PENGENDALIAN HAMA PADI SAWAH PASCA INTRODUKSI TEKNOLOGI PENGENDALIAN HAMA TERPADU - SUPRIATNA, ADE; SADIKIN, IKIN (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 1 Februari 2004)
This study was conducted in 1998 and took place in Karawang as center of West Java's rice production and as representation of rice farm in Java’s north coast. The objectives of study were to describe the appearance of the farmer in controlling pest after introducing Integrated Pest Management (IPM) technology, to analyze the cost of pest control and its effect on both production and in come, and to measure the pesticide residues in grain as a final product. The result showed that some components of IPM technology as preventive against the pest exploding have adopted by the farmers. Forty eight percent of the farmers have applied the insecticide based on IPM concept. The cost of pest control was Rp.94,000 (9% of total cost) consisting of pesticide cost (64%) and applying cost (36%)/ha/season. The number of pesticide applied by the Non IPMT farmer was higher than that of IPMT farmer but they did not influence to production and in come. The result of chemical analysis showed that some pesticide residues have pound but their concentration were still under Maximum Residue Limits (MRL) namely BPMC and endosulfan. The others were not detected such as sipermetrin, deltametrin, monocrotophos, diazinon, carbopuran, calbaril, etc. because their concentration was still too low. Nevertheless, the residues of undegradable pesticide applied by the farmer in the past time have still found namely aldrin and DDT.
Keywords: Wet Rice, Pesticide Residue, Production, Income, and West Java.